Six shorts 2017 : the finalists for the 2017 Sunday Times EFG Short Story Award /: the finalists for the 2017 Sunday Times EFG Short Story Award. (2017) - Alcott, Kathleen; Johnston, Bret Anthony; Lambert, Richard; Lodato, Victor; Ng, Celeste; Rooney, Sally
No abstract available